2013
DOI: 10.1118/1.4842556
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI defined subvolumes of a brain metastatic lesion by principle component analysis and fuzzy-c-means clustering for response assessment of radiation therapy

Abstract: Purpose: To develop a pharmacokinetic modelfree framework to analyze the dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) data for assessment of response of brain metastases to radiation therapy. Methods: Twenty patients with 45 analyzable brain metastases had MRI scans prior to whole brain radiation therapy (WBRT) and at the end of the 2-week therapy. The volumetric DCE images covering the whole brain were acquired on a 3T scanner with approximately 5 s temporal resolution and a total scan time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…78 To maintain AIF's enhancement feature, some studies used only a certain number or percentage of voxels based on the peak enhancement ratio in AIF generation. 60,78 However, such a method is sensitive to the absolute CA concentration value, and the data reproducibility may be reduced when intensity-based image reconstructed methods were used. In this work, we selected a group of voxels based on the timeto-peak distribution and average the resultant time course to create AIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 To maintain AIF's enhancement feature, some studies used only a certain number or percentage of voxels based on the peak enhancement ratio in AIF generation. 60,78 However, such a method is sensitive to the absolute CA concentration value, and the data reproducibility may be reduced when intensity-based image reconstructed methods were used. In this work, we selected a group of voxels based on the timeto-peak distribution and average the resultant time course to create AIF.…”
Section: Discussionmentioning
confidence: 99%
“…Then a histogram of each arterial structure voxel's time-topeak (T max ) was generated. 60 Next, the T max of the C p (t) was determined by the peak position of the generated histogram, and the C p (t) was calculated by averaging the CA concentration of the voxels that constituted the histogram's peak.…”
Section: Pharmacokinetics Analysismentioning
confidence: 99%
“…The curves need to be preprocessed to remove variations in intensity magnitude and onset time of contrast enhancement because of individual hemodynamics and various acquisition protocols. A signal intensity change at time t , Δ S ( t ), after contrast injection compared with a baseline intensity, ( S 0 ), is computed, and then normalized to the peak of the arterial input function ( AIF max ) of the patient as shown in the study by Farjam et al (11) and using the following equation: normalΔnormalSfalse(normaltfalse)=normalSfalse(normaltfalse)-S0normalS0normalΔSNfalse(normaltfalse)=normalΔnormalSfalse(normaltfalse)1AIFmax where S ( t ) is the signal intensity of a DCE curve at time t , Δ S N ( t ) is normalized S ( t ), and AIF max is the peak enhancement in Δ S ( t ) of the AIF. The AIF was determined by thresholding the intensity changes in a region of interest in a large artery, for example, carotid artery in this study.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…As an alternative to more formal pharmacokinetic modelling, analysis of the shape of concentration-time signal curves may present a simplification for DCE-MR applications (Woolf, Padhani et al 2014(Farjam, Tsien et al 2014)(Stoyanova, Huang et al 2012) For breast cancer patients treated with neoadjuvant chemotherapy prior to surgery and RT, changes in signal curve shape after chemotherapy correlated with pharmacokinetic model output, and with clinical and pathological response (Woolf, Padhani et al 2014). This has been further formalized using a principal component analysis approach, which demonstrated that much of the response-related information in DCE-MR curves of brain metastases is contained within the first projection coefficient, corresponding to the area-under-the-curve (Farjam, Tsien et al 2014).…”
mentioning
confidence: 97%
“…)(Farjam, Tsien et al 2014)(Stoyanova, Huang et al 2012) For breast cancer patients treated with neoadjuvant chemotherapy prior to surgery and RT, changes in signal curve shape after chemotherapy correlated with pharmacokinetic model output, and with clinical and pathological response (Woolf, Padhani et al 2014). This has been further formalized using a principal component analysis approach, which demonstrated that much of the response-related information in DCE-MR curves of brain metastases is contained within the first projection coefficient, corresponding to the area-under-the-curve (Farjam, Tsien et al 2014). More recently, principal component analysis applied to DCE-MR data in a preclinical tumor model found that the second projection coefficient corresponded to 18 FMISO-PET time activity curves and ex vivo pimonidazole stained tissue sections (Stoyanova, Huang et al 2012).…”
mentioning
confidence: 98%